An international agreement with full participation to tackle the stock of greenhouse gases - Uwe Kratzsch; Gernot Sieg; Ulrike Stegemann (Technische Universität Braunschweig, Institut für Volkswirtschaftslehre, 2011)
This paper analyzes greenhouse gas emissions that build up an atmospheric stock which depreciates over time. Weakly renegotiation- proof and subgame perfect equilibria in a game of international emission reduction exist if countries put a sufficiently high weight on future payoffs, even though there is a discontinuity in the required discount factor due to the integrity of the number of punishing countries. Treaties are easier to reach if the gas depreciates slowly.
Keywords: Q54; F53; H41; 330; global warming; international agreement; weak renegotiation-proofness; Klimaschutz; Umweltabkommen; Verhandlungstheorie; Treibhausgas; Luftverunreinigung; Theorie